PENGARUH KONSENTRASI DAN LAMA PERENDAMAN TELUR DALAM LARUTAN KOLKHISIN TERHADAP LAJU PERTUMBUHAN IKAN PATIN (PANGASIUS PANGASIUS) - PRISTIA R, PRANANTA (Universitas Negeri Surabaya, 2013)
Catfish is one of popular fish being consumed. Therefore it requires an effort to improve fish quality productions. Colchicine is one of the reagents for mutation that causes polyploid, organisms that have three or more sets of chromosomes in their cells. Hence, they are sterile. The purpose of this study was to determine the effect of concentration of colchicine and immersion duration of eggs in colchicine solution to the growth rate of catfish. The research was conducted experimentally using a completely randomized design (CRD) with two treatment factors. The first factor was the concentration of colchicine of 0 ppm, 0.5 ppm and 1 ppm. The second was the immersion duration of eggs in the colchicine solution for 15 minutes, 20 minutes and 25 minutes. Each combination of factors was repeated three times so that there were 27 samples of treatments. The data obtained were the specific growth rate (SGR) and analyzed descriptively. The results showed that concentration of colchicine solution and egg immersion duration influence the growth rate of catfish. The highest specific growth rate was obtained by the combination of 1 ppm of colchicine concentration and 25 minutes of immersion duration.   Key words: Colchicine concentration; eggs immersion duration; specific growth rate (SGR) of catfish